Influence of altered Ca-P based electrolytes on the anodised titanium bioactivity - Alipal, J.; Lee, T. C.; Koshy, P.; Abdullah, H. Z.; Idris, M. I. (Elsevier, 2021)
Anodic oxidation (AO) of titanium is a common electrochemical process for surface modification of metallic surfaces and is conducted in an electrolyte solution. Anodisation of titanium implants can generate a coating with optimal characteristics to accelerate the growth of bone-like apatite. The present work aims to develop a novel AO electrolyte formulation of a Ca–P base solution containing three different alteration agents. The characteristics of the anodised coating were modified by varying the volume fractions of the alteration agents, namely sulphuric acid, hydrogen peroxide, and acetic acid in a base solution of β-glycerolphosphate disodium salt pentahydrate (β-GP) and calcium acetate monohydrate (CA). The surface morphology, mineralogy, wettability, and bioactivity of these coatings were analysed using scanning electron microscopy (SEM), X-ray diffraction (XRD), contact angle analysis, and in vitro testing using simulated body fluid (SBF). Anodisation in a mixture of β-GP + CA electrolyte resulted in the formation of Ca-P-rich oxide coating (with surface features with a donutlike shape) and when altered with 12.5 vol% sulphuric acid, highly defined spiky needle-like morphology was seen on the surface. These coatings were composed of hydroxyapatite, tricalcium phosphate, and calcium diphosphate. After 7 days of SBF immersion, the surface was observed to contain a dense layer of bone-like apatite. However, alteration using acetic acid did not result in any significant changes to the surface characteristics and no bone-like apatite formation was observed even after soaking in SBF for 7 days. Alteration using hydrogen peroxide resulted in an anodised coating that assisted the growth of bone-like apatite layer on the coating surfaces after soaking in SBF for 7 days. The differences in coating performance are linked to the presence of different functional ions with hydronium groups (from sulphuric acid) being superior compared to the carboxyl ions (from acetic acid). The coating produced by sulphuric acid alteration demonstrated super hydrophilicity and roughe